THE pH AND ABSORPTION OF CADMIUM IN ALMONDS OF ORGANIC COCOA (Theobroma cacao L.), IN LEONCIO PRADO, HUÁNUCO, PERÚ - FLORIDA ROFNER, Nelino (2018)
The type of soil has an important influence on the availability and absorption of cadmium by the cacao plant (Theobroma cacao L.), in particular the pH, the % of clay and the amount of Mg2+ and Zn present in the soil. Therefore, the objective was to measure the influence of soil pH on the absorption levels of cadmium in CCN-51 cocoa beans in the Leoncio Prado - Huánuco province, for which 20 agricultural parcels were selected from the members of Cooperativa Cacao Alto Huallaga, which complied with all the norms and techniques of organic production. 20 soil samples and 20 samples of almonds were analyzed. The results show that the average pH of the soil was 5.68; the cadmium available in the soil was 0.32 µg g-1 and the cadmium content in the cocoa almonds of the 20 samples analyzed yielded 0.98 µg g-1. The investigation concludes that the values ​​of cadmium in almonds are above the maximum level allowed by the European Union and a negative correlation was found between the pH of the soil and the content of cadmium in cocoa almonds (R2 = 0.0522), not finding a dependence of cadmium in almonds, with respect to the pH of the soil, this requires further research to determine the factors involved in this process.